2020
DOI: 10.1126/sciadv.aay8937
|View full text |Cite
|
Sign up to set email alerts
|

Retinol-binding protein 2 (RBP2) binds monoacylglycerols and modulates gut endocrine signaling and body weight

Abstract: Expressed in the small intestine, retinol-binding protein 2 (RBP2) facilitates dietary retinoid absorption. Rbp2-deficient (Rbp2−/−) mice fed a chow diet exhibit by 6-7 months-of-age higher body weights, impaired glucose metabolism, and greater hepatic triglyceride levels compared to controls. These phenotypes are also observed when young Rbp2−/− mice are fed a high fat diet. Retinoids do not account for the phenotypes. Rather, RBP2 is a previously unidentified monoacylglycerol (MAG)-binding protein, interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 72 publications
2
45
0
Order By: Relevance
“…Rbp2 −/− mice maintained normal serum retinol levels. Also, there were no genotypedependent differences in all-trans-retinoic acid levels in the liver, white adipose tissue, or fasting and nonfasting intestinal tissue (9). These findings clearly indicate the previously unanticipated role of CRBP2 in energy homoeostasis on both the small intestinal and systemic levels.…”
supporting
confidence: 50%
See 3 more Smart Citations
“…Rbp2 −/− mice maintained normal serum retinol levels. Also, there were no genotypedependent differences in all-trans-retinoic acid levels in the liver, white adipose tissue, or fasting and nonfasting intestinal tissue (9). These findings clearly indicate the previously unanticipated role of CRBP2 in energy homoeostasis on both the small intestinal and systemic levels.…”
supporting
confidence: 50%
“…Purification of human CRBP2 was performed essentially as described previously (9). The synthetic clone of cDNA (NP_004155.2; Origene Technologies) was inserted into pET3b vector (Novagen).…”
Section: Expression and Purification Of Crbp2mentioning
confidence: 99%
See 2 more Smart Citations
“…RBP2 (SLP=3.14) is expressed in the gut and its product is responsible for uptake of vitamin A but recent studies in mice have shown that it also influences body weight, the response to glucose challenge and hepatic triglyceride levels while Rbp2 deficient mice have increased adiposity, with larger adipocytes, and decreased energy expenditure (Lee et al, 2020). The authors suggest a signalling role for RBP2 and if similar mechanisms were present in humans then it is plausible that variants disrupting RBP2 could lead to increased risk of hyperlipidaemia.…”
Section: Resultsmentioning
confidence: 99%